Gestão de riscos ecológicos na exploração de petróleo na camada do pré-sal : as tomadas de decisão a partir do princípio da precaução - Grassi, Viviane (My University, 2015)
The present research deals with the management of ecological risks in exploration of oil in the pre-salt layer, focusing on the incidence of the precautionary principle, as well as at the opening of the decision-making processes for the popular participation. The study starts with the analysis of the instruments defining the energetic matrix from the Brazilian petroleum, in the context of the recent discovery of large sources of fossil fuel. Intends to contribute to the critical reflection on the possibility to reduce ecological risks through social participation, given the scientific uncertainties arising from techniques for exploitation of this resource. The analysis uses theoretical lenses of the precautionary principle, evaluates the participatory instruments promoted by ANP (hearings and public consultations), after the discovery of oil in the pre-salt layer. In response to the initial yearning, were used the inductive method that contemplated: the bibliographical research, in order to offer theoretical basis about the principles of environmental law applicable; legislative research, presenting the regulatory framework; and the documentary and exploratory research, using official publications of the committees and councils of ministries and regulatory agencies, about risk management in the context of decision-making on oil energy matrix. It was found that there was no public incentives for the participation of society in decision-making processes in the oil production and extraction. It was also noticed, in addiction, there was no effective participation in hearings/public consultations of the society. In these procedures, according to the searched overviews, there were only the participation of representatives of national and international oil companies, institutes and associations of private enterprise and of Petrobras. It is concluded that there is a deficit of popular participation in decision-making in public policy concerning the energy matrix.
A presente pesquisa trata da gestão de riscos ecológicos na exploração de petróleo na camada do Pré-sal, com enfoque na incidência do princípio de precaução, bem como na abertura dos processos decisórios à participação da sociedade. O trabalho começa com a análise dos instrumentos definidores da matriz energética advinda do petróleo brasileiro, no contexto da recente descoberta de grandes fontes desse combustível fóssil. Pretende contribuir com a reflexão crítica sobre a possibilidade de redução dos riscos ecológicos por meio da participação social, diante das incertezas científicas decorrentes das técnicas para exploração deste recurso. A análise utiliza as lentes teóricas do princípio da precaução, avalia os instrumentos participativos promovidos pela ANP (audiências e consultas públicas), após a descoberta do petróleo da camada do Pré-sal. Para dar resposta ao anseio inicial foi utilizado o método indutivo, que contemplaram: a pesquisa bibliográfica, no sentido de oferecer embasamento teórico acerca dos princípios de direito ambiental aplicáveis; a pesquisa legislativa, apresentando de maneira panorâmica o marco regulatório; e a pesquisa documental e exploratória a partir das publicações oficiais dos comitês e conselhos de Ministérios e agências reguladoras, acerca da gestão de riscos, no contexto dos processos decisórios na matriz energética petrolífera. Verificou-se que, além de não haver incentivo público para a participação da sociedade nos processos decisórios na Produção e Extração (P&E) de petróleo, não há participação efetiva em audiências/consultas públicas da sociedade. Nestes procedimentos, de acordo com as sumulas pesquisadas, há apenas a participação de representantes de petrolíferas nacionais e internacionais, institutos e associações da iniciativa privada e da Petrobrás. Conclui-se que há um déficit de participação popular na tomada de decisões em políticas públicas concernentes à matriz energética.
Keywords: Direito ambiental; Política pública; Meio ambiente; Petróleo; Environmental law; Public policy; Environment; Petroleum